Minat Belajar Pemrograman pada Mahasiswa Lulusan SMK dan Non SMK di Prodi PTIK - Rista Rusdianawati (Universitas Muhammadiyah Sidoarjo, 2017)
This research aims to describe the student interest in learning programming at two different educational background, vocational high school and non-vocational high school graduates. The sample are all students of the Education of Information and Communication Technology Study Program in Universitas Muhammadiyah Sidoarjo (UMSIDA) academic year 2014/2015 up to 2016/2017 which involved 41 people. The data are collected by distributing questionnaires to the respondents. The collected data are analyzed by using descriptive statistical techniques with the norm percentage. The results showed that (1) the learning interest of vocational high school graduates has an average percentage of 73.04% with medium/enough category; and (2) the learning interest of non-vocational high school graduates has an average of 74.34% with medium/enough category. There are four results if it is observed from each dimension shaping the learning interest of students graduated from vocational high school, namely: (1) the dimensions of interest has a mean of 75.57% with medium category; (2) the dimensions of attention by 73.58%; (3) the dimensions of consciousness by 73.86%; and (4) the dimensions of the curiosity of 68.41%. While the average in each dimension obtained from non-vocational high school graduate are (1) the dimensions of interest of 76.53%; (2) the dimensions of attention by 78.62%; (3) the dimensions of awareness by 75%; and (4) the dimensions of the curiosity of 66.84%.